Parent Coach: The Utilization Of The Score Model For Children’s Cognitive, Affective, And Conative Development - Geofakta RAZALI; Wulan FURRIE; Alo LILIWERI; Alexander SERAN (Indonesia Strategic Sustainability, 2023)
Communication that does not run smoothly will cause miscommunication. In family communication that is carried out between parents and children, if miscommunication is not immediately resolved, there will be communication congestion. One way to solve this problem is through coaching. In this case, parents become a coach for their children, which is called a